Sandwich-type AFB1 electrochemical detection kit and detection method based on porous Au@Pd nanocore-shell structure

Through the "Aptamer-antibody" sandwich-type AFB1 electrochemical detection kit based on porous Au@Pd nanocore-shell structure, the existing AFB1 detection methods are solved, and AFB1 detection is achieved with high sensitivity and good selectivity, which is suitable for fast real-time detection of food and medicinal materials.

CN114894848BActive Publication Date: 2025-04-08HENAN UNIV OF CHINESE MEDICINE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210446804.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-26
Publication Date
2025-04-08
Estimated Expiration
2042-04-26

AI Technical Summary

Technical Problem

The existing AFB1 detection method has the disadvantages of complex experimental process, long consumption time, and expensive equipment, making it difficult to achieve detection effects with good selectivity, high stability, simple operation and high detection sensitivity.

Method used

The "aptagon-antibody" sandwich-type AFB1 electrochemical detection kit based on the porous Au@Pd nanocore-shell structure is used to improve the surface area of ​​the electrode and the amplification ability of the electrical signal through the assembly of MWCNTs/CMK-3/AuNPs nanocomposites and Au@PdNPs-Ab-Tb bioconjugates.

Benefits of technology

High sensitivity detection of AFB1 was achieved, with the detection limit reaching 0.24 fg/mL, and the current intensity of the modified electrode could still be maintained at 97.76% of the initial value after 14 days, with good reproducibility and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114894848B_ABST
    Figure CN114894848B_ABST
Patent Text Reader

Abstract

The present invention discloses a sandwich-type AFB1 electrochemical detection kit and a detection method based on a porous Au@Pd nanocore-shell structure, wherein the kit comprises GCE, HAuCl4, trisodium citrate, MWCNTs, CMK‑3, chitosan, HDPC, K2PdCl4, AA, Aptamer, Antibody, Tb, and MCH. The present invention successfully prepares an electrochemical detection kit capable of accurately, sensitively, and specifically detecting AFB1 by assembling nanomaterials such as AuNPs, MWCNTs, CMK‑3, and porous Au@PdNPs, as well as two recognition elements (Ab, Ap) with strong affinity for AFB1. In the range of 20fg / mL to 2ng / mL, the logarithm of the AFB1 concentration is positively correlated with the current intensity, and the linear equation is: I(μA)=9.836×10 ‑6 ×lg(C AFB1 )+7.346×10 ‑6 (R 2 =0.996), the detection limit (LOD) was 0.24 fg / mL, and the reproducibility and selectivity were good. The method also showed satisfactory results in the detection of AFB1 in actual samples. Therefore, the method of the present invention has good application potential in the detection of AFB1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an "aptamer-antibody" sandwich-type AFB1 electrochemical detection kit and a detection method based on a porous Au@Pd nano core-shell structure, belonging to the technical field of bioanalysis. Background Art

[0002] Aflatoxin B1 (AFB1) is a common and widely distributed mycotoxin with strong biological toxicity. Continuous intake of trace amounts of AFB1 by the human body can cause chronic poisoning, growth disorders, fibrotic lesions and other symptoms. In addition, AFB1 also has extremely strong carcinogenic, teratogenic and mutagenic effects. Considering the risks and threats of AFB1, highly sensitive detection of AFB1 in food and medicinal materials is of great significance in the fields of medicine, pathology, clinical analysis, food testing, etc.

[0003] There are many commonly used AFB1 detection methods, such as thin layer chromatography, liquid chromatography, enzyme-linked immunosorbent assay, etc. However, most of these methods have the disadvantages of complex experimental process, long time consumption, expensive equipment, etc. Therefore, it is very necessary to develop an AFB1 detection method with good selectivity, high stability, simple operation and high detection sensitivity.

[0004] In recent years, aptamers have been widely used in various biomolecule detections due to their advantages of low cost, stable chemical properties, easy modification, simple preparation, and effective identification of ion targets. When electrochemical aptamer sensors are used to detect analytes, aptamers can specifically bind to the analytes and cause changes in their own spatial structure, thereby causing changes in electrical signals such as current, and ultimately establishing a relationship between electrical signals and the analytes. However, traditional electrodes have a small surface area and limited binding capacity for the analyte. Therefore, the present invention aims to construct a new AFB1 detection kit with the advantages of high sensitivity, good selectivity, and high stability, so as to achieve rapid real-time detection of AFB1 in food and Chinese medicinal materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an "aptamer-antibody" sandwich-type AFB1 electrochemical detection kit and detection method based on a porous Au@Pd nanocore-shell structure, which has the advantages of high sensitivity, good selectivity and high stability.

[0006] In order to achieve the above object, one of the technical solutions of the present invention is:

[0007] An "aptamer-antibody" sandwich-type AFB1 electrochemical detection kit based on a porous Au@Pd nanocore-shell structure includes: GCE, HAuCl4, trisodium citrate, MWCNTs, CMK-3, chitosan, HDPC, K2PdCl4, AA, Aptamer, Antibody, Tb, MCH, ultrapure water, anhydrous ethanol, glacial acetic acid, and PBS buffer.

[0008] Furthermore, some raw materials need to be prepared into solutions when used, among which the concentration of HAuCl4 solution is 1mM or 10mM, the concentration of trisodium citrate solution is 38.8mM, the concentration of AA solution is 100mM, the concentration of K2PdCl4 solution is 10mM, the concentration of Aptamer solution is 1μM, the concentration of MCH solution is 2mM, the concentration of Antibody solution is 50μg / mL, the mass fraction of acetic acid solution is 2%, and the concentration of PBS buffer is 0.1M (pH=7.4).

[0009] The sequence of Aptamer is 5′-SH-(CH2)6-GTTGGGCACGTGTTGTCTCTCTGTGTCTCGTGCCTTCGCTAGGCCCACA-3′.

[0010] One of the technical solutions of the present invention is: a method for detecting AFB1, comprising the following steps:

[0011] (1) MWCNTs / CMK-3 / AuNPs nanocomposite was dropped onto the GCE surface for reaction;

[0012] (2) adding the aptamer to the electrode surface in step (1) and reacting;

[0013] (3) immersing the electrode in step (2) in an MCH solution for reaction;

[0014] (4) dropping the sample to be tested onto the surface of the electrode in step (3) to react;

[0015] (5) dropping the Au@PdNPs-Ab-Tb bioconjugate onto the electrode surface of step (4) to react;

[0016] (6) Place the electrode in step (5) in PBS buffer and measure the electrochemical signal.

[0017] Further, the preparation method of MWCNTs / CMK-3 / AuNPs nanocomposite material is:

[0018] 50mL of 1mM HAuCl4 solution was heated to boiling; then 10mL of 38.8mM trisodium citrate solution was added and kept boiling until the color of the solution no longer changed, cooled to room temperature, and the AuNPs suspension was collected; 4.8mg of MWCNTs, 4.8mg of CMK-3 and 19.2mg of chitosan were dispersed in 4mL of 2% acetic acid solution by mass, and ultrasonically treated in an ice-water bath to obtain a uniformly dispersed nanomaterial mixture; finally, 4mL of the AuNPs suspension was added to the 4mL nanomaterial mixture, and the entire mixed system was ultrasonically treated to obtain a uniformly dispersed MWCNTs / CMK-3 / AuNPs nanocomposite material.

[0019] Further, the preparation method of Au@PdNPs-Ab-Tb bioconjugate is:

[0020] ① Add 0.1g HDPC, 0.5mL 10mM HAuCl4 solution and 2mL 10mM K2PdCl4 solution into 25mL ultrapure water to form a uniform mixed solution under ultrasonic conditions; then add 1.5mL 100mM AA solution into the mixed solution to react, then centrifuge and wash the reaction product Au@PdNPs, and then disperse it in 10mL ultrapure water to obtain Au@PdNPs suspension;

[0021] ② Add 20 μL of 50 μg / mL Antibody solution to 1 mL of Au@PdNPs suspension and incubate to obtain Au@PdNPs-Ab conjugate solution; then, add 3 mg of Tb to the Au@PdNPs-Ab conjugate solution and incubate; then, centrifuge to remove unreacted antibody Antibody and Tb to obtain Au@PdNPs-Ab-Tb bioconjugate, rinse with PBS buffer and then disperse in 1 mL of PBS buffer.

[0022] Furthermore, the reaction conditions of step ① are: shaking reaction for 3 hours at 35° C. in the dark; and the incubation conditions of step ② are: shaking incubation for 3-12 hours at 37° C.

[0023] Furthermore, the reaction temperature of steps (1), (3)-(5) is 37°C and the reaction time is 30min-1h; the reaction conditions of step (2) are: overnight at room temperature; and step (5) is to measure the electrochemical signal using square wave voltammetry (SWV) with a scanning range of -0.6 to 0V, a rising potential of 0.004V, a pulse amplitude of 0.025V, and a frequency of 15Hz.

[0024] Furthermore, the GCE is pre-treated, and the pre-treatment method is: polishing the GCE to a mirror surface, cleaning, drying, and setting aside.

[0025] One of the technical solutions of the present invention is: an application of the above-mentioned kit in detecting aflatoxin B1.

[0026] The schematic diagram of the detection method of the present invention is as follows Figure 1 shown.

[0027] Beneficial effects of the present invention:

[0028] 1. MWCNTs / CMK-3 / AuNPs nanocomposites are used as substrate materials to provide a large number of binding sites for thiolated aptamers; the porous Au@Pd core-shell nanostructures can be used as nanocarriers to load a large number of capture probes Ab and electroactive substances Tb. AFB1 can be accurately captured through the high affinity of antibodies and aptamers to the target. Due to the specific recognition of antibody-antigen, a large number of tracers Au@PdNPs-Ab-Tb are assembled on the electrode surface, greatly amplifying the current intensity, thereby improving the sensitivity of detection.

[0029] 2. MWCNTs / CMK-3 / AuNPs nanocomposite materials formed a stable and dense conductive active layer on the surface of the glassy carbon electrode, significantly enhancing the electron transfer ability of the electrode.

[0030] 3. By assembling nanomaterials such as AuNPs, MWCNTs, CMK-3 and porous Au@PdNPs, as well as two recognition elements (Ab and Ap) with strong affinity for AFB1, an electrochemical detection kit capable of accurately, sensitively and specifically detecting AFB1 was successfully prepared. The experimental results showed that in the range of 20fg / mL to 2ng / mL, the logarithm of AFB1 concentration was positively correlated with the current intensity, and its linear equation was: I(μA)=9.836×10 -6 ×lg(C AFB1 )+7.346×10 -6 (R 2 =0.996), the detection limit (LOD) was 0.24fg / mL; after the modified electrode was stored for 14 days, the current intensity could still maintain 97.76% of the initial value, with good reproducibility and selectivity. The method also showed satisfactory results in the detection of AFB1 in actual samples. Therefore, the method of the present invention has good application potential in the detection of AFB1. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the detection method of the present invention.

[0032] Figure 2 A is the SEM image of AuNPs; B is the TEM image of AuNPs; C is the UV-visible absorption spectrum of AuNPs; D is the DLS image of AuNPs.

[0033] Figure 3 A is the SEM image of MWCNTs; B is the SEM image of CMK-3; C is the SEM image of MWCNTs / CMK-3 / AuNPs; D is the TEM image of MWCNTs / CMK-3 / AuNPs; E is the EDS image of MWCNTs / CMK-3 / AuNPs.

[0034] Figure 4 A is the SEM image of Au@PdNPs; B is the TEM image of Au@PdNPs; C is the STEM-HAADF image of Au@PdNPs; D is the EDS image of Au@PdNPs; E is the DLS image of Au@PdNPs.

[0035] Figure 5 A is the SWV diagram of the modified electrode under different modification conditions; B is the Nyquist diagram of the electrode layer-by-layer assembly process; C is the CV diagram of the modified electrode under different modification conditions.

[0036] Figure 6 A is the SEM image of the bare glassy carbon electrode; B is the SEM image after modification with MWCNTs / CMK-3 / AuNPs; C is the SEM image after modification with MWCNTs / CMK-3 / AuNPs / Ap / MCH / AFB1 / Au@PdNPs-Ab-Tb.

[0037] Figure 7 A is the modification volume optimization of MWCNTs / CMK-3 / AuNPs; B is the reaction time optimization of AFB1; C is the reaction time optimization of Au@PdNPs-Ab-Tb.

[0038] Figure 8 A is the SWV response signal of AFB1 at different concentrations; B is the linear relationship between the current signal and the logarithm of AFB1 concentration.

[0039] Fig. 9 Comparison of SWV response signals of the same concentrations of AFB1, AFB2, AFG1, AFG2, OTA and blank group under the same detection conditions. DETAILED DESCRIPTION

[0040] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.

[0041] Aptamer was purchased from Shanghai Bioengineering Co., Ltd. and has the sequence of 5′-SH-(CH2)6-GTTGGGCACGTGTTGTCTCTCTGTGTCTCGTGCCTTCGCTAGGCCCACA-3′ (SEQ ID NO. 1).

[0042] The antibody was aflatoxin B1 polyclonal antibody (anti-aflatoxin B1 rabbit antibody), purchased from Sigma-Aldrich.

[0043] Example 1: "Aptamer-antibody" sandwich-type AFB1 electrochemical detection kit based on porous Au@Pd nanocore-shell structure

[0044] The invention discloses an "aptamer-antibody" sandwich-type AFB1 electrochemical detection kit based on a porous Au@Pd nanocore-shell structure, comprising the following raw materials: GCE (glassy carbon electrode), tetrachloroauric acid (HAuCl4), trisodium citrate, MWCNTs (multi-walled carbon nanotubes), CMK-3 (ordered mesoporous carbon), chitosan, hexadecylpyridinium chloride monohydrate (HDPC), potassium chloropalladate (K2PdCl4), L-ascorbic acid (AA), aptamer (Aptamer), antibody (Antibody), toluidine blue (Tb), 6-mercapto-1-hexanol (MCH), ultrapure water, anhydrous ethanol, glacial acetic acid, and PBS buffer.

[0045] Some raw materials need to be prepared into solutions when used, among which the concentration of HAuCl4 solution is 1mM or 10mM, the concentration of trisodium citrate solution is 38.8mM, the concentration of AA solution is 100mM, the concentration of K2PdCl4 solution is 10mM, the concentration of Aptamer solution is 1μM, the concentration of MCH solution is 2mM, the concentration of Antibody solution is 50μg / mL, the mass fraction of acetic acid solution is 2%, and the concentration of PBS buffer is 0.1M (pH=7.4).

[0046] Example 2: Preparation of MWCNTs / CMK-3 / AuNPs nanocomposite

[0047] Place 50 mL of 1 mM HAuCl4 aqueous solution in a 150 mL round-bottom flask, stir evenly and heat to boiling; then quickly add 10 mL of 38.8 mM trisodium citrate aqueous solution and keep boiling until the color of the solution no longer changes; remove the heat source, cool to room temperature, and collect the AuNPs suspension;

[0048] 4.8 mg MWCNTs, 4.8 mg CMK-3 and 19.2 mg chitosan were dispersed in 2% acetic acid solution (4 mL) and ultrasonically treated in an ice-water bath for 1.5 h until a uniformly dispersed nanomaterial mixture was obtained. Finally, 4 mL of AuNPs suspension was added to the above 4 mL of nanomaterial mixture, and the entire mixed system was ultrasonically treated for 1 h to obtain a uniformly dispersed MWCNTs / CMK-3 / AuNPs nanocomposite material.

[0049] (1) Structural characterization of AuNPs:

[0050] ① Morphology and particle size characterization

[0051] The surface of AuNPs was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 2 A and Figure 2 As shown in Figure B, AuNPs are uniformly spherical with a particle size of about 19 nm. The particle size distribution is uniform and monodisperse. The particle size of AuNPs was measured by a nanoparticle size zeta potential analyzer (DLS). The results showed that the particle size distribution was around 20 nm ( Figure 2 D), which is consistent with the TEM results.

[0052] ② UV-visible absorption spectroscopy characterization

[0053] The AuNPs were characterized by UV-visible absorption spectroscopy. Figure 2 As shown in Figure C, AuNPs showed a characteristic absorption peak of nano-gold at 520 nm, indicating that AuNPs were successfully prepared.

[0054] (2) Structural characterization of MWCNTs / CMK-3 / AuNPs:

[0055] The surface morphology of MWCNTs / CMK-3 / AuNPs was characterized by SEM, TEM and EDS (energy dispersive spectrometry). Figure 3 As shown in A, MWCNTs are densely stacked and present a tubular structure with alternating coiling and twisting. Figure 3 As shown in B, CMK-3 has a highly ordered nanorod array porous fiber structure, with a large number of mesopores between the carbon nanorods and a large specific surface area. Figure 3 C shows that the array of CMK-3 has been superimposed on the curled MWCNTs, and a large number of spherical AuNPs are scattered on its surface. TEM image ( Figure 3 D) further illustrates that MWCNTs and CMK-3 can stack with each other through π-π interaction, and then adsorb AuNPs through electrostatic interaction to form MWCNTs / CMK-3 / AuNPs nanocomposites. EDS results are shown in Figure 3 As shown in Figure E, the MWCNTs / CMK-3 / AuNPs nanocomposite is composed only of Au and C elements. These results indicate that the MWCNTs / CMK-3 / AuNPs nanocomposite was successfully prepared.

[0056] Example 3: Preparation of Au@PdNPs-Ab-Tb bioconjugate

[0057] (1) 0.1 g HDPC, 0.5 mL 10 mM HAuCl4 solution and 2 mL 10 mM K2PdCl4 solution were added to 25 mL ultrapure water to form a uniform mixed solution under ultrasonic conditions; then 1.5 mL of freshly prepared 100 mM AA solution was quickly added to the mixed solution, and the mixture was shaken for 3 h at 35 °C in the dark. Finally, the reaction product Au@PdNPs was centrifuged (10000 rpm, 10 min), washed with ultrapure water and dispersed again in 10 mL ultrapure water to obtain an Au@PdNPs suspension;

[0058] (2) Add 20 μL of 50 μg / mL Antibody (Ab) solution to 1 mL Au@PdNPs suspension and incubate at 37°C with shaking for 3 h (200 rpm) to obtain Au@PdNPs-Ab conjugate solution; then, add 3 mg Tb to the Au@PdNPs-Ab conjugate solution and incubate at 37°C with shaking overnight (300 rpm); then, centrifuge (10000 rpm, 10 min) to remove unreacted antibody Antibody and Tb to obtain Au@PdNPs-Ab-Tb bioconjugate, rinse with PBS buffer and then disperse in 1 mL PBS buffer.

[0059] Structural and morphological characterization of Au@PdNPs:

[0060] The structure and morphology of Au@PdNPs were characterized by SEM and TEM. Figure 4 A~4C show that Au@PdNPs present a spherical nanoscale core-shell structure with many vertical pores, uniform particle size distribution, and good dispersion. EDS was used to characterize Au@PdNPs. The results are shown in Figure 4 D shows that Au@PdNPs are composed of Au and Pd elements only. DLS was used to characterize Au@PdNPs. Figure 4 As shown in Figure E, the particle size distribution of the core-shell nanostructure is uniform. These results indicate that Au@PdNPs have been successfully synthesized.

[0061] Example 4: Construction of detection method

[0062] (1) Electrode pretreatment

[0063] The bare GCE electrode was placed on the suede and polished with 0.03 μm polishing powder until a polished mirror surface was obtained. Then, it was ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water for 1 min in sequence, and dried with nitrogen gas for later use.

[0064] (2) Electrode modification

[0065] ① 1.5 μL of MWCNTs / CMK-3 / AuNPs nanocomposite was added dropwise to the GCE surface and reacted at 37°C for 30 min;

[0066] ② Add 5 μL of 1 μM aptamer Aptamer (Ap) dropwise onto the electrode surface in step ① and react at room temperature overnight;

[0067] ③ Soak the electrode in step ② in 300 μL MCH solution and react at 37°C for 30 min to block the unbound nonspecific sites;

[0068] ④ Add 5 μL of the sample to be tested (containing AFB1) to the surface of the electrode in step ③, react at 37°C for 30 min, wash away the uncaptured AFB1 with ultrapure water, and blow dry with nitrogen;

[0069] ⑤ Add 5 μL Au@PdNPs-Ab-Tb bioconjugate to the electrode surface in step ④ and react at 37°C for 1 h;

[0070] ⑥ Place the electrode in step ⑤ in 0.1M PBS buffer (pH=7.4) and perform electrochemical measurement using square wave voltammetry (SWV) with a scan range of -0.6 to 0 V, a rising potential of 0.004 V, a pulse amplitude of 0.025 V, and a frequency of 15 Hz.

[0071] Example 5: Feasibility test

[0072] In order to verify the feasibility of this method, SWV was used to characterize the current response of the electrode under different modification conditions. Figure 5 As shown in Figure A, when the modification of Ap (curve a), AFB1 (curve b) and Au@PdNPs-Ab-Tb (curve c) was lacking, no obvious current response was observed (except for a weak background signal), while a clear current signal (curve d) could be observed at around -0.3V for the fully modified electrode. This shows that the kit cannot be successfully assembled if any step is missing during the construction of the modified electrode, while the fully modified kit can accurately capture AFB1 and successfully connect the tracer Au@PdNPs-Ab-Tb, thereby showing a clear current intensity in the SWV measurement. The above results show that the "aptamer-antibody" sandwich-type AFB1 electrochemical detection kit based on the porous Au@Pd nanocore-shell structure is feasible for detecting AFB1.

[0073] Example 6: Characterization

[0074] The modified electrode was placed in 5 mM [Fe(CN)6] 3- / 4-In the electrolyte solution, electrochemical impedance spectroscopy (EIS) was used to characterize the gradual modification process of the electrode surface. The semicircle diameter of the high-frequency area in the Nyquist plot represents the impedance value Rct of the modified electrode, which corresponds to the electrode surface [Fe(CN)6] 4- / 3- The electron transfer ability of the probe. Figure 5 As shown in Figure B, when MWCNTs / CMK-3 / AuNPs are modified onto the electrode, its Rct decreases rapidly (~130.0Ω, curve b) compared with the bare GCE (~201.2Ω, curve a), which is mainly due to the large specific surface area and outstanding conductive properties of the MWCNTs / CMK-3 / AuNPs nanocomposite. After Ap modification, due to the PO4 3- Inhibition of the redox probe [Fe(CN)6] 4- / 3- Charge transfer on GCE leads to an increase in its Rct (~299.8Ω, curve c); after modification with MCH, a denser film is formed on the electrode surface, which further hinders the electron transfer ability of the electrode surface, thereby increasing Rct continuously (~503.1Ω, curve d); after Ap specifically captures AFB1, the Rct value of the electrode continues to increase (~716.8Ω, curve e), which indicates that the electron transfer resistance on the electrode surface further increases; after the addition of Au@PdNPs-Ab-Tb, Ab specifically recognizes AFB1 and connects with it, resulting in a significant increase in Rct (~955.7Ω, curve f). These results show that the modified electrode proposed in the present invention is successfully prepared.

[0075] In addition, the cyclic voltammetry curves corresponding to each step of the electrode modification process are shown in Figure 5 As shown in Figure C, GCE forms a stable and dense conductive active layer due to the modification of MWCNTs / CMK-3 / AuNPs nanocomposite materials, so its current intensity (curve b) is larger than that of bare GCE (curve a); when the electrode is modified by non-conductive Ap, the conductivity of the electrode surface decreases slightly, which significantly reduces the current intensity (curve c); the self-assembly of MCH also reduces the current intensity on the electrode surface (curve d); with the addition of AFB1, the current intensity further decreases due to its combination with Ap, which increases the steric hindrance on the GCE surface (curve e); finally, when Au@PdNPs-Ab-Tb captures AFB1, the significantly increased steric hindrance seriously affects the charge transfer, resulting in a significant decrease in current intensity (curve f). The CV results are basically consistent with the EIS results, further verifying the successful construction of the modified electrode.

[0076] Scanning electron microscopy (SEM) was used to characterize the surface morphology of the modified electrode. Figure 6 As shown, the unmodified bare GCE exhibits a flat and smooth surface ( Figure 6A). After the electrode is modified, the surface is filled with a large amount of dense MWCNTs / CMK-3 / AuNPs nanocomposites ( Figure 6 B). Finally, after all materials were modified, a large amount of Au@PdNPs-Ab-Tb bioconjugates were added to the electrode surface on the basis of the original surface ( Figure 6 C).

[0077] The above results indicate that the modified electrode has been successfully prepared.

[0078] Example 7: Optimization of detection conditions

[0079] In order to achieve the best detection performance of the kit, the present invention optimizes important parameters such as the modification volume of MWCNTs / CMK-3 / AuNPs, the reaction time of AFB1, and the reaction time of Au@PdNPs-Ab-Tb.

[0080] (1) Modification volume optimization of MWCNTs / CMK-3 / AuNPs

[0081] The performance of the conductive film layer formed by the nanocomposite on the electrode surface is closely related to the signal amplification performance of the kit. Therefore, the relationship between the modified volume of the nanocomposite and the current response of the kit was studied. Figure 7 As shown in Figure A, as the modified volume of MWCNTs / CMK-3 / AuNPs gradually increases, the current intensity also gradually increases, reaching the maximum value at 1.5μL, and when the volume exceeds 1.5μL, the current intensity gradually decreases. This is because when the volume of the nanocomposite material becomes larger, the conductive film layer formed on the GCE surface will be too thick, reducing the electron transfer rate. Therefore, 1.5μL is selected as the optimal modification volume of MWCNTs / CMK-3 / AuNPs.

[0082] (2) Optimization of AFB1 reaction time

[0083] Appropriate AFB1 reaction time can maximize the amount of antibody modification, thereby ensuring signal amplification. Figure 7 As shown in Figure B, the current intensity increases sharply with the increase of reaction time within 10 to 30 minutes, which means that as the reaction time increases, more and more AFB1 is captured by the modified electrode and reaches saturation after 30 minutes. Therefore, 30 minutes is selected as the optimal reaction time for AFB1.

[0084] (3) Optimization of the reaction time of Au@PdNPs-Ab-Tb

[0085] like Figure 7As shown in Figure C, within 10 to 60 minutes, the current signal gradually increased with the increase of time. After 60 minutes, the current signal became flat, indicating that Au@PdNPs-Ab-Tb had fully reacted with AFB1 and reached a saturated state. Therefore, the optimal reaction time of Au@PdNPs-Ab-Tb was 60 minutes.

[0086] Example 8: Analytical Performance

[0087] According to the optimal experimental conditions optimized in Example 7, the current intensity of the kit under different concentrations of AFB1 was studied to evaluate the dynamic response range and sensitivity of the detection kit. Figure 8 As shown in A, the peak current gradually increased with the increase of AFB1 concentration. Figure 8 As shown in B, in the range of 20 fg / mL to 2 ng / mL, the logarithm of AFB1 concentration is positively correlated with the current intensity. The linear regression equation is I (μA) = 9.836 × 10 -6 ×lg(C AFB1 )+7.346×10 -6 (R 2 =0.996), and the limit of detection (LOD) was 0.24 fg / mL (S / N=3). The results showed that the detection kit had high sensitivity and low detection limit, and had good performance.

[0088] Example 9: Selectivity, stability and reproducibility

[0089] According to the optimal experimental conditions obtained in Example 7, a selective experiment was carried out. The present invention detected the current intensity of four structural analogs of AFB1, aflatoxin B2 (AFB2), aflatoxin G1 (AFG1), aflatoxin G2 (AFG2), ochratoxin A (OTA) and a blank solution (TE) under the same conditions (all concentrations were 2 ng / mL). The results are as follows Fig. 9 As shown, the current signals of AFB2, AFG1, AFG2 and OTA were 23.30%, 25.76%, 23.17% and 24.61% of AFB1 respectively, and the current signal of the blank group was 78.06% lower than that of AFB1. The results show that the detection kit of the present invention has good selectivity for the detection of AFB1, which is mainly due to the fact that the detection method uses two recognition elements (Ap and Ab) with strong affinity.

[0090] In addition, in order to verify the stability of the method, the modified electrode constructed was stored at 4°C for 14 days and then tested. It was found that the current intensity at this time could still be maintained at 97.76% of the initial value. This shows that the modified electrode prepared by the present invention has good stability. The reproducibility of the electrode was evaluated by intra-group and inter-group experiments (n=6), and the RSD within the group and between the groups were 2.65% and 3.09% respectively. The results show that the modified electrode has good reproducibility.

[0091] Example 10: Actual sample testing

[0092] AFB1 of known concentration (200pg / mL, 20pg / mL and 2pg / mL) was added to actual samples (corn, malt, Chinese yam, Achyranthes bidentata, Rehmannia root, Chrysanthemum, Quisqualis chinensis and Semen Platycladi) and tested according to the optimal experimental conditions obtained in Example 7. The results are shown in Table 1. The recovery rate of the kit was 93.83% to 106.29%, and the RSD (relative standard deviation) was 0.42% to 7.38%. The results show that the prepared kit is reliable and effective in detecting AFB1 in actual samples.

[0093] Table 1. Recovery results of AFB1 detected in actual samples (n=3)

[0094] Sequence Listing <110> Henan University of Traditional Chinese Medicine <120> Sandwich-type AFB1 electrochemical detection kit and detection method based on porous Au@Pd nanocore-shell structure <160> 1 <170> SIPOSequenceListing 1.0 <210> 1 <211> 49 <212> DNA <213> Artificial Sequence <400> 1 gttgggcacg tgttgtctct ctgtgtctcg tgccttcgct aggcccaca 49

Claims

1. An "aptamer-antibody" sandwich type AFB1 electrochemical detection kit based on a porous Au@Pd nanocore-shell structure, characterized in that: include: Glassy carbon electrode GCE, tetrachloroauric acid HAuCl4, trisodium citrate, multi-walled carbon nanotubes MWCNTs, ordered mesoporous carbon CMK-3, chitosan, hexadecylpyridinium chloride monohydrate HDPC, potassium chloropalladate K2PdCl4, L-ascorbic acid AA, aptamer Aptamer, antibody Ab, toluidine blue Tb, 6-mercapto-1-hexanol MCH; The sequence of Aptamer is 5′-SH-(CH2)6-GTTGGGCACGTGTTGTCTCTCTGTGTCTCGTGCCTTCGCTAGGCCCACA-3′; Ab is a polyclonal antibody against aflatoxin B1; The assembly process of the kit comprises the following steps: (1) Dropping MWCNTs / CMK-3 / AuNPs nanocomposite onto the GCE surface for reaction; (2) Add the aptamer to the electrode surface in step (1) and react; (3) Soaking the electrode in step (2) in MCH solution for reaction; (4) Add the sample to be tested to the surface of the electrode in step (3) for reaction; (5) dropping the Au@PdNPs-Ab-Tb bioconjugate onto the electrode surface of step (4) to react; (6) placing the electrode in step (5) in PBS buffer and measuring the electrochemical signal; The preparation method of MWCNTs / CMK-3 / AuNPs nanocomposite material is as follows: Heat 50 mL of 1 mM HAuCl4 solution to boiling; then add 10 mL of 38.8 mM trisodium citrate solution and keep boiling until the color of the solution no longer changes, cool to room temperature, and collect the AuNPs suspension; disperse 4.8 mg MWCNTs, 4.8 mg CMK-3 and 19.2 mg chitosan in 4 mL of 2% acetic acid solution by mass, and ultrasonicate in an ice-water bath to obtain a uniformly dispersed nanomaterial mixture; finally, add 4 mL of AuNPs suspension to 4 mL of nanomaterial mixture, and continue to ultrasonicate the entire mixed system to obtain a uniformly dispersed MWCNTs / CMK-3 / AuNPs nanocomposite material; The preparation method of Au@PdNPs-Ab-Tb bioconjugate is as follows: ① Add 0.1 g HDPC, 0.5 mL 10 mM HAuCl4 solution and 2 mL 10 mM K2PdCl4 solution into 25 mL ultrapure water to form a uniform mixed solution under ultrasonic conditions; then add 1.5 mL 100 mM AA solution into the mixed solution to react, then centrifuge and wash the reaction product Au@PdNPs, and then disperse it in 10 mL ultrapure water to obtain Au@PdNPs suspension; ② Add 20 μL of 50 μg / mL Ab solution to 1 mL of Au@PdNPs suspension and incubate to obtain Au@PdNPs-Ab conjugate solution; then, add 3 mg of Tb to the Au@PdNPs-Ab conjugate solution and incubate; then, centrifuge to remove unreacted antibody Ab and Tb to obtain Au@PdNPs-Ab-Tb bioconjugate, rinse with PBS buffer and then disperse in 1 mL of PBS buffer.

2. The kit according to claim 1, characterized in that It also includes ultrapure water, anhydrous ethanol, glacial acetic acid, and PBS buffer.

3. The kit according to claim 1, characterized in that During the assembly process, some raw materials need to be prepared into solutions, among which the concentration of Aptamer solution is 1 μM and the concentration of MCH solution is 2 mM.

4. A method for detecting AFB1 using the kit according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Dropping MWCNTs / CMK-3 / AuNPs nanocomposite onto the GCE surface for reaction; (2) Add the aptamer to the electrode surface in step (1) and react; (3) Soaking the electrode in step (2) in MCH solution for reaction; (4) Add the sample to be tested to the surface of the electrode in step (3) for reaction; (5) dropping the Au@PdNPs-Ab-Tb bioconjugate onto the electrode surface of step (4) to react; (6) Place the electrode prepared in step (5) in PBS buffer and measure the electrochemical signal.

5. The method according to claim 4, characterized in that The preparation method of MWCNTs / CMK-3 / AuNPs nanocomposite material is as follows: Heat 50 mL of 1 mM HAuCl4 solution to boiling; then add 10 mL of 38.8 mM trisodium citrate solution and keep boiling until the color of the solution no longer changes, cool to room temperature, and collect the AuNPs suspension; disperse 4.8 mg MWCNTs, 4.8 mg CMK-3 and 19.2 mg chitosan in 4 mL of 2% acetic acid solution, and ultrasonically treat it in an ice-water bath to obtain a uniformly dispersed nanomaterial mixture. Finally, add 4 mL of AuNPs suspension to 4 mL of nanomaterial mixture, and continue to ultrasonically treat the entire mixed system to obtain a uniformly dispersed MWCNTs / CMK-3 / AuNPs nanocomposite material.

6. The method according to claim 4, characterized in that The preparation method of Au@PdNPs-Ab-Tb bioconjugate is as follows: ① Add 0.1 g HDPC, 0.5 mL 10 mM HAuCl4 solution and 2 mL 10 mM K2PdCl4 solution into 25 mL ultrapure water to form a uniform mixed solution under ultrasonic conditions; then add 1.5 mL 100 mM AA solution into the mixed solution to react, then centrifuge and wash the reaction product Au@PdNPs, and then disperse it in 10 mL ultrapure water to obtain Au@PdNPs suspension; ② Add 20 μL of 50 μg / mL Ab solution to 1 mL of Au@PdNPs suspension and incubate to obtain Au@PdNPs-Ab conjugate solution; then, add 3 mg of Tb to the Au@PdNPs-Ab conjugate solution and incubate; then, centrifuge to remove unreacted antibody Ab and Tb to obtain Au@PdNPs-Ab-Tb bioconjugate, rinse with PBS buffer and then disperse in 1 mL of PBS buffer.

7. The method according to claim 6, characterized in that The reaction conditions of step ① are: shaking reaction at 35°C in the dark for 3 h; the incubation conditions of step ② are: shaking incubation at 37°C for 3-12 h.

8. The method according to claim 4, characterized in that The reaction temperature of steps (1), (3) to (5) is 37°C and the reaction time is 30 min-1 h. The reaction conditions of step (2) are: overnight at room temperature. Step (5) uses square wave voltammetry (SWV) to measure the electrochemical signal with a scan range of -0.6 to 0 V, a rising potential of 0.004 V, a pulse amplitude of 0.025 V, and a frequency of 15 Hz.

9. The method according to claim 4, characterized in that GCE is first pre-treated, and the pre-treatment method is: polishing GCE to a mirror surface, cleaning, drying, and setting aside.

10. Use of the kit according to any one of claims 1 to 3 in detecting aflatoxin B1.

Citation Information

Patent Citations

  • Method for preparing aptamer sensor used for simultaneously detecting two kinds of mycotoxin

    CN108267572A

  • Preparation methods and detection methods of nanocomposite and ZEN electrochemical aptamer sensor

    CN109470761A